IMPLEMENTASI API PADA SISTEM INFORMASI TAGIHAN LISTRIK DENGAN MODEL EXTREME PROGRAMMING (STUDI KASUS: PLTS KANTIN UNIVERSITAS PAMULANG) - Aldi Husadif; Niki Ratama (Journal of Research and Publication Innovation, 2023)
Solar Power Plants (PLTS) are used in the Pamulang University environment, especially canteens in the Pamulang University environment. However, information processing related to PLTS electricity bills still uses a manual system. So that billing data processing, data entry, information search related to electricity bills received by canteen owners are not yet effective and efficient. For this reason, an electricity bill information system is needed that can manage billing data, data entry, search for information related to PLTS electricity bills. In this study using the model extreme programming consists of planning, design, implementation, and testing. The system is built using the Laravel framework and MySQL database. This research was able to produce a system that can manage billing, data entry as well as search for information related to PLTS bills. The resulting system has been tested through a testing black box where all functions work properly.